Mechanical and Microstructure Characteristic of Oil- based Drilling Cuttings as Mineral Powder Substitute in Hot Mix Asphalt Mixture - Abdulsamad, Balen Z.; Muhialdin, Ameen A.; Hawez, Tolaz S.; Ibrahim, Rahel K. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Beyond the intensive worldwide oil wells drilling activities for seeking energy, the amount of oil-based drilling cuttings (OBDC) increased significantly, OBDC defined as a wasted drilling mud which is used in the drilling operation of oil wells. The OBDC falls under the category of hazardous waste that contains heavy metals and radioactive elements. In this study, OBDC was used as a substitute of mineral powder in hot mix asphalt. Various doses of OBDC (0%, 25%, 50%, 75%, and 100% by weight) were employed to replace the mineral powder. Marshall specimens were prepared to assess the physical characteristics and examine the microstructure. In results, by employing OBDC to 100%, The Marshall stability decreased from 12.1 kN to 9.22 kN, and flow value decreased from 3.96 mm to 3.3 mm compared to control specimen (0% of OBDC) due to the presence of uncoated and agglomeration of large amount of OBDC particle in bitumen constituent as examined by scanning electron microscope. Air voids increase from 3.9% to 4.26% and voids in mineral aggregates increase from 14.63% to 15.20% when mineral powder replaced by OBDC filler from 0% to 100%, respectively, due to the difference between the specific gravity of OBDC and mineral powder, in which higher percentage of OBDC leads to increase the porosity of the specimen. Utilizing 100% of OBDC instead of the mineral powder is compromised because the result falls within the standard ranges.